Anti-breast carcinoma effects of green synthesized tin nanoparticles from Calendula officinalis leaf aqueous extract inhibits MCF7, Hs 319.T, and MCF10 cells proliferation. Issue 1 (31st December 2022) - Zhai, Chao; Shi, Cheng; Hu, Yanli; Xu, Zhongxin; Wang, Ruiying
Abstract: In this study, tin nanoparticles were green synthesized using the aqueous extract of Calendula officinalis . Different techniques such as FE-SEM, XRD, FT-IR, and EDS analysis were used to characterize SnNPs@ C. officinalis . A 21.87 nm was obtained for the crystal size of the tin nanoparticles using XRD analysis. The FE-SEM images show a spherical morphology for SnNPs@ C. officinalis with a range size of 21.63–64.07 for the synthetic nanoparticles. The anti-breast cancer effects of biologically synthesized SnNPs@ C. officinalis against breast cancer cell lines were assessed. The anti-breast cancer properties of the SnNPs@ C. officinalis could significantly remove the MCF7, Hs 319.T, and MCF10 cancer cell lines in a time and concentration-dependent manner by MTT assay. The antioxidant activity of SnNPs@ C. officinalis was determined by the DPPH method. The SnNPs@ C. officinalis showed the highest antioxidant activity according to the IC50 value. It seems the anti-human breast cancer effect of recent nanoparticles is due to their antioxidant effects.